I Love Us For Real: Black Mother Leadership and Early Learning Spaces - Fearon, Stephanie (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
Increasingly, literature affirms the integral role Black mothers play in cultivating humanizing learning spaces for young Black children. Such work recognizes the epistemic injustices Black mothers and their children endure in early childhood education and care programs. Despite Black mothers’ prominence in their children’s lives, limited research explores the ways Black mothers’ leadership supports the well-being of young Black children in early learning settings. This arts-informed autoethnography draws on literature and personal stories to investigate how the author, a Black mother scholar, reaffirmed her maternal leadership while attending a child and family early learning program in Ontario.